Invisibility by design : women and labor in Japan's digital economy - Lukács, Gabriella (Duke University Press, 2020)
"INVISIBILITY BY DESIGN examines Japanese women's Internet-based entrepreneurship in the late 1990s. Disadvantaged by a long recession, and entrenched in a historically patriarchal and discriminatory labor marketplace, many Japanese women in the late 1990s and early 2000s turned to Internet commerce as an alternative to the traditional labor market. Drawing from Marxist and neo-Marxist theories of labor, as well as ethnographic research with Japanese women bloggers, net idols, cell phone novelists, and online traders, Gabriella Lukács's book explores how, in the context of Japanese women's online labor practices, the search for meaningful work drove innovations in capitalist accumulation--in this case, Internet-driven labor and market practices. By anchoring her research in the "feminized" space of online DIY entrepreneurship, Lukács's INVISIBILITY BY DESIGN traces how the development of digital economies utilizes pre-existing local economic inequalities. Positioning these women's online DIY businesses at the intersection of affective labor and intellectual labor, this book thus highlights the ways in which various identities shape whose labor is gendered, made visible, and recognized as productive. Lastly, this book deploys theories of assemblage to theorize the relationship between young women, the technologies they use, and their audiences in terms of "techno-social assemblages," and argues that metaphors of "seduction and duplicity"--More than metaphors of "domination and resistance"--best describe the relationship between actants and participants in these techno-social assemblages"--